Efficacy and Safety of Dexmedetomidine for Postoperative Delirium in Adult Cardiac Surgery on Cardiopulmonary Bypass - Park, Jae Bum (The Korean Society for Thoracic and Cardiovascular Surgery, 2014)
BACKGROUND: Delirium after cardiac surgery is associated with serious long-term negative outcomes and high costs. The aim of this study is to evaluate neurobehavioral, hemodynamic, and sedative characteristics of dexmedetomidine, compared with the current postoperative sedative protocol (remifentanil) in patients undergoing open heart surgery with cardiopulmonary bypass (CPB). METHODS: One hundred and forty two eligible patients who underwent cardiac surgery on CPB between April 2012 and March 2013 were randomly divided into two groups. Patients received either dexmedetomidine (range, 0.2 to 0.8 μg/kg/hr; n=67) or remifentanil (range, 1,000 to 2,500 μg/hr, n=75). The primary end point was the prevalence of delirium estimated daily via the confusion assessment method for intensive care. RESULTS: When the delirium incidence was compared with the dexmedetomidine group (6 of 67 patients, 8.96%) and the remifentanil group (17 of 75 patients, 22.67%) it was found to be significantly less in the dexmedetomidine group (p<0.05). There were no statistically significant differences between two groups in the extubation time, ICU stay, total hospital stay, and other postoperative complications including hemodynamic side effects. CONCLUSION: This preliminary study suggests that dexmedetomidine as a postoperative sedative agent is as sociated with significantly lower rates of delirium after cardiac surgery.